The Impact of Mind Mapping-Based Health Promotion on Adolescents' Self-Awareness of Smoking Cessation - Wini Hadiyani; Neng Sahar (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2022)
Self-awareness to stop smoking is needed by teenagers so that the increase in the number of teen smokers can be overcome. Mind Mapping, one of the methods used in health promotion is a health intervention. The goal of this study is to see how the mind mapping method affects adolescents' self-awareness of smoking cessation. Methods: this research used a quasi-experimental design with the a two-group pre-post test. Questionnaire used Emotional Self Awareness Scale (ESAS). This research shows that there was a significant influence of mind mapping method on self-awareness with p value 0.00. In Conclusion, mind mapping method can be an option in health promotion to reduce smoking behavior in adolescents.